Statistical relations features between changes of Caribbean Sea surface temperatures and solar activity - Холопцев, О. В.; Нікіфорова, М. П. (Харківський національний університет імені В.Н.Каразіна, 2014)
Paper deals with statistical relations between Caribbean sea surface temperature variations and solar activity. With the use of correlation analysis between time series of mean year temperatures changes, their anomalies index and Wolf numbers, hypothesis of the Caribbean Sea surface temperatures variations delay caused by solar activity changes was tested. It was found that the features of sub-Antarctic intermediate waters circulation of the Atlantic Ocean cause the presence of a significant statistical relations between Caribbean Sea average surface temperatures changes and solar activity variations, that are advancing them approximately on 200 years. Developed ultralong-range forecast of Caribbean Sea average surface temperatures changes show that until the middle of the XXI century downward trend will dominate, and further, to the end of it, – upward. Работа посвящена исследованию статистических связей вариаций поверхностных температур Карибского моря и солнечной активности. С помощью корреляционного анализа рядов изменений среднегодовых температур рассматриваемой области, индекса их аномалий, а также чисел Вольфа проверялась гипотеза о запаздывании вариаций поверхностных температур Карибского моря, вызванных изменениями солнечной активности. Установлено, что особенности циркуляции субантарктических промежуточных вод Атлантического океана обуславливают наличие значимой статистической связи изменений средних поверхностных температур Карибского моря с вариациями солнечной активности, опережающими их приблизительно на 200 лет. Из разработанного с учетом этой связи сверхдолгосрочного прогноза изменений средних поверхностных температур Карибского моря следует, что до середины ХХI в. будут преобладать тенденции к их снижению, а далее, до его окончания, будет происходить их повышение. Робота присвячена дослідженню статистичних зв'язків варіацій поверхневих температур Карибського моря і сонячної активності. За допомогою кореляційного аналізу рядів змін середньорічних температур розглянутій області, індексу їх аномалій, а також чисел Вольфа перевірялася гіпотеза про запізнення варіацій поверхневих температур Карибського моря, викликаних змінами сонячної активності. Встановлено, що особливості циркуляції субантарктичних проміжних вод Атлантичного океану обумовлюють наявність значущого статистичного зв'язку змін середніх поверхневих температур Карибського моря з варіаціями сонячної активності, випереджаючими їх приблизно на 200 років. З розробленого з урахуванням цього зв'язку понаддовгострокового прогнозу змін середніх поверхневих температур Карибського моря випливає, що до середини ХХI в. будуть переважати тенденції до їх зниження, а далі, до його закінчення, відбуватиметься їх підвищення.